Using interactive learning objects in teaching accounting sciences: a case study - Gaviria-Rodríguez, Diana; Arango-Arango, Juan; Valencia-Arias, Alejandro; Verde Flores, Lilian Janet; Valencia, Jackeline; Zavala, Luisa Rodríguez (Frontiers in Education, 2024)
Interactive learning objects (ILOs) are tools that can enhance and promote teaching in various fields of knowledge. For instance, GeoGebra is a free educational software designed for teaching and learning mathematics. It is an interactive mathematical software that can help students better understand accounting concepts and visualize complex financial relationships, making it easier to learn abstract concepts. Additionally, it can be used to explore what-if financial scenarios, which can help students develop their decision-making skills. The purpose of this article is to investigate the impact of GeoGebra on the development of mathematical skills among accounting science students. It contributes to the literature by demonstrating the effectiveness of teaching financial concepts through the application of five linear functions and their mathematical relationships in GeoGebra. This approach bridges the gap between differential calculus knowledge and the ability to achieve a geometric understanding and interpretation of the lines that can be created with this dynamic software. It also enables the interpretation of financial statement concepts based on the variations of the lines. GeoGebra, a mathematical software, will feature a Comprehensive Income Statement (CIS) as one of its relevant financial statements in financial accounting. Starting with an equation containing 15 variables, two are selected to represent the abscissa and ordinate axes, while the remaining 13 are considered parameters that can be adjusted by the user in the OIA windows. By changing these values, the equation will produce a straight line. It is worth noting that using OIA can be an effective strategy for enhancing one's understanding of basic sciences. The study emphasizes the significance of accuracy in financial management, the interplay among variables, and the utilization of technological tools to aid in comprehending these concepts.